(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2019)
Even with the evolution of chemotherapeutic procedures and agents, chemotherapy may cause certain side effects that impair the patients’ quality of life. The aim of this review is to isolate and describe the side effects arising only from chemotherapy. This paper comprises an extensive review of the main side effects affecting the health status of patients undergoing chemotherapy procedures. In addition, Cancer patients experience a variety of symptoms that can be physical or psychological. These symptoms may vary in terms of occurrence, severity, and distress and can be the result of the illness or the treatment.